The Belief of al-Qaḍā and al-Qadr in Islamic Theological Discourse - Fauzan Saleh (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
The emergence of Muhammadiyah and Persatuan Islam in 1912 and 1923, respectively, representing the Islamic reform movement in the early twentieth century, constituted a response popular costums. The Islamic religious reforms advocated by these movements encompassed several aspects of life, individual well as social. However, the primary concern voiced by the reformists was with certain theological issues which were essential to the whole movement.DOI: 10.15408/sdi.v8i3.682